Globalisation And Public Policy In Nigeria: Challenges And Prospects - Arugu, Love; Jacob, Ogedi (Advances in Social Sciences Research Journal, 2020)
This paper attempts to look at the impact of globalisation on public policy as it affects the economic development in Nigeria. The main proposition of this paper is that Nigeria cannot comfront the challenges of contemporary globalisation without a sustained effort to develop her economic foundations. This is because globalisation will most likely be utilitarian if its end can foster domestic development agenda. The paper was anchored on the Marxist Theory of State. The import of this approach to the paper is that it proceeds from a holistic examination of the country’s historical experience and its implication for the present day political economy. The research design was historical-descriptive research design and the data were obtained through secondary sources. Content analysis was used in analyzing the data obtained. The paper concludes that many poor countries like Nigeria liberalised its economy without adequate preparation and precaution. The paper recommended inter-alia that Nigeria should formulate economic policies that recognises her specific needs and circumstances in order to promote inclusive economic development.